Protocol for Exercise Hemodynamic Assessment: Performing an Invasive Cardiopulmonary Exercise Test in Clinical Practice. (1st December 2015) - Berry, Natalia C.; Manyoo, Agarwal; Oldham, William M.; Stephens, Thomas E.; Goldstein, Ronald H.; Waxman, Aaron B.; Tracy, Julie A.; Leary, Peter J.; Leopold, Jane A.; Kinlay, Scott; Opotowsky, Alexander R.; Systrom, David M.; et al.
Abstract : Invasive cardiopulmonary exercise testing (iCPET) combines full central hemodynamic assessment with continuous measurements of pulmonary gas exchange and ventilation to help in understanding the pathophysiology underpinning unexplained exertional intolerance. There is increasing evidence to support the use of iCPET as a key methodology for diagnosing heart failure with preserved ejection fraction and exercise‐induced pulmonary hypertension as occult causes of exercise limitation, but there is little information available outlining the methodology to use this diagnostic test in clinical practice. To bridge this knowledge gap, the operational protocol for iCPET at our institution is discussed in detail. In turn, a standardized iCPET protocol may provide a common framework to describe the evolving understanding of mechanism(s) that limit exercise capacity and to facilitate research efforts to define novel treatments in these patients.